MODAL ANALYSIS OF A TENNIS RACQUET - Haron, Mohd Amin (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
This project is carried out to investigate the behavior of tennis racquet with varying parameters and to obtain the modal characteristics of a tennis racquet. Modal analysis is the study of the dynamic properties of structures under vibrational excitation. In this project, the structure put to the test is a tennis racquet. Tennis racquet is subjected to a force from the velocity of the tennis ball when it is hit. This paper presents structural and modal analysis for a tennis racquet under certain assumptions which had been set. The scope of the project has been narrowed down to develop modal parameters of a tennis racquet with respect to natural frequency and mode shape. This project also examined the behavior of the model subjected to different forces at different locations with varying materials. In this project, ANSYS software was used for the analysis on the tennis racquet. The methods used in this project were structural and modal analysis, both using ANSYS for modeling and simulation. The findings are reported and based on the data; the natural frequency of the model is obtained and compared to the theoretical values. Recommendation is pointed out as the outcome of the project which can be further continued by selecting maximum values of the racquet standard as well as conducting analysis on more different materials.